The second virial coefficients for normal fluids Their estimation, new approach and correlations - MoraCasal, René (Editorial Universidad Nacional (EUNA), 2018)
The second virial coefficient is a relevant property for determining the effect of the non-ideality of real gases, applicable to the vast majority of existing chemical and industrial processes. An Analysis of the most relevant correlations, based on a new approach. This book can be used by students, researchers and professionals interested in a both the fundamentals and the most advanced aspects of the subjects, as well as in the application to chemical process calculations.